Dipping in Cygnus X-2 in a multi-wavelength campaign due to absorption of extended ADC emission - Balucinska-Church, M.; Schulz, N. S.; Wilms, Jörn; Gibiec, A.; Hanke, Manfred; Spencer, R. E.; Rushton, A.; Church, M. J. (Astronomy & Astrophysics, 2011)
We report results of one-day simultaneous multiwavelength observations of Cygnus X-2 using XMM, Chandra, the European VLBI Network and the XMM Optical Monitor. During the observations, the source did not exhibit Z-track movement, but remained in the vicinity of the soft apex. It was in a radio quiescent/quiet state of <150 mu Jy. Strong dip events were seen as 25% reductions in X-ray intensity. The use of broadband CCD spectra in combination with narrow-band grating spectra has now demonstrated for the first time that these dipping events in Cygnus X-2 are caused by absorption in cool material in quite a unique way. In the band 0.2-10 keV, dipping appears to be due to progressive covering of the Comptonized emission of an extended accretion disk corona, the covering factor rising to 40% in deep dipping with an associated column density of 3 x 10(23) atom cm(-2). Remarkably, the blackbody emission of the neutron star is not affected by these dips, in strong contrast with observations of typical low mass X-ray binary dipping sources. The Chandra and XMM gratings directly measure the optical depths in absorption edges such as Ne K, Fe L, and O K and a comparison of the optical depths in the edges of non-dip and dip data reveals no increase of optical depth during dipping even though the continuum emission sharply decreases. Based on these findings, at orbital phase 0.35, we propose that dipping in this observation is caused by absorption in the outer disk by structures located opposite to the impact bulge of the accretion stream. With an inclination angle >60 degrees these structures can still cover large parts of the extended ADC, without absorbing emission from the central neutral star.
Keywords: accretion; accretion disks; acceleration of particles; stars: neutron; X-rays: binaries; X-rays: individuals: Cyg X-2; radio continuum: general